Sistem Pendidikan, dan Tenaga Pendidikan (Literatur Manajemen Pendidikan Islam) - Mulyana Saputri; Susilawati Susilawati; Saihul Abid; Yusmiati Yusmiati; Madyan Madyan (STEKOM PRESS, 2024)
Previous research or relevant research is very important in research or writing scientific articles. Previous research or relevant previous research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Islamic Education Management influencing the Education System, Education Management and Education Personnel. The purpose of writing this article is to build a hypothesis for further development. The results of this literature review article are: First, educational personnel influence Islamic education management, second, educational management influences Islamic education management, and third, the education system influences Islamic education management.